Building an AI That Feels: AI systems with emotional intelligence could learn faster and be more helpful - Czerwinski, Mary; Hernandez, Javier; McDuff, Daniel (IEEE Spectrum, 2021)
In the past year, have you found yourself under stress? Have you ever wished for help coping? Imagine if, throughout the pandemic, you'd had a virtual therapist powered by an artificial intelligence (AI) system, an entity that empathized with you and gradually got to know your moods and behaviors. Therapy is just one area where we think an AI system that can recognize and interpret emotions could offer great benefits to people.